(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
This article presents a contribution to the theme of urban planning in small Brazilian cities, focusing on the elaboration of Master Plans after the constitutional obligation, established by the Estatuto da Cidade, Law 10.257/2001. To fulfill this objective, methodologically based on a case study, the objective is to develop a critical analysis of the Municipal Development Master Plan (PDDM) of the municipality of Amargosa - Bahia - Brazil, instituted in 2006 due to the end of the five-year period. established by the Estatuto for municipalities included in the obligation to review or prepare Master Plans. With modest administrative structures and reduced technical and instrumental preparation, in Brazil, the conditions for small towns to successfully carry out basic urban planning and management practices are limited. Remaining at the level of discourse, urban planning in small towns materializes the abyss between rhetoric (represented by a law, a plan, a project) and practice. Keywords: Urban planning; Small towns; Estatuto da Cidade; Master plan; Amargosa – BA.